Evaluation of a lysis-centrifugation and biphasic bottle blood culture system during routine use. - Kelly, M T (1983)
An in-use evaluation of a commercially available lysis-centrifugation blood culture system (Isolator; Du Pont Co., Wilmington, Del.) is presented. The Isolator was compared with biphasic bottles containing Trypticase soy broth and agar for the detection of organisms in 3,129 paired blood samples. Of 272 potential pathogens recovered, 78% were detected by the Isolator system, and 69% were detected by the biphasic bottle. A total of 31% of these organisms were detected only by the Isolator, and 22% were detected only by the biphasic bottle. The Isolator demonstrated enhanced detection of facultative gram-negative bacilli, anaerobic bacteria, and polymicrobial cultures. The biphasic bottle was more effective for the recovery of facultative gram-positive cocci, especially Streptococcus pneumoniae. The two systems were equally effective for the recovery of yeasts. Contamination rates were 3% for the Isolator and 3.2% for the biphasic bottle. The results indicate that the Isolator system performs well in routine clinical use, but it should be complemented by another method to obtain optimal detection of bacteremia. The biphasic bottle provides an acceptable complementary system both in terms of utility and performance.